2017
DOI: 10.1097/scs.0000000000003263
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Sinus Pneumatization Affects Height of the Lateral Lamella and Position of Anterior Ethmoidal Artery

Abstract: Preoperative evaluation of the frontal sinus (FS) and associated anatomical structures may reduce the risk of intraoperative complications and facilitate the management of potential complications. In this study, the authors aimed to evaluate relationship between FS pneumatization and critical anatomical structures. Paranasal sinus computerized tomography scans of 350 sides of 175 patients were evaluated. The pneumatization pattern of the FS, FS dimensions (on the axial, coronal, and sagittal slices), anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
1
18
2
1
Order By: Relevance
“…The effects of the pneumatization pattern of FS on olfactory fossa depth are still a matter of debate. Comoglu et al reported a deeper olfactory fossa in overpneumatized FSs, which was in contrast to our study. In their study, they also investigated the association of the anterior ethmoid artery; however, their data did not include the other paranasal sinus types with pneumatization defect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The effects of the pneumatization pattern of FS on olfactory fossa depth are still a matter of debate. Comoglu et al reported a deeper olfactory fossa in overpneumatized FSs, which was in contrast to our study. In their study, they also investigated the association of the anterior ethmoid artery; however, their data did not include the other paranasal sinus types with pneumatization defect.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, medial displacement of orbit in patients with MS hypoplasia was evident in the report by Ozcan et al In these recent studies, the touchstone of the method was evaluation of the structures upon paranasal CT scans because paranasal CT was suggested to be the gold standard technique for evaluation of paranasal sinuses . The association between FS pneumatization and olfactory fossa was at the center of several prior studies, but we also focused on olfactory fossa depth and lateral lamella length in patients with MS and SS hypoplasia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…5) A few studies have reported a direct relationship between the pneumatization of FS and the LLL. 1,2) In contrast, another study has reported that lesser the pneumatization of the FS, greater is the LLL. 3) These results could be a matter of contention.…”
Section: Introductionmentioning
confidence: 92%
“…There is limited literature between the relation of the degree of FS pneumatization and the development of the PNS structures. [1][2][3][4] Lateral lamella length (LLL) and olfactory fossa depth are important anatomical parameters to be considered in preventing surgical complications like skull base injury. Greater LLL increases the possibility of lateral lamella injury during the surgery.…”
Section: Introductionmentioning
confidence: 99%